Priorities and strategies for improving Roma women's access to primary health care services in cases on intimate partner violence: a concept mapping study - Carmen Vives-Cases; Isabel Goicolea; Alison Hernández; Belen Sanz-Barbero; MCarmen Davó-Blanes; Daniel La Parra-Casado (BMC, 2017)
Abstract Background With an explicit focus on Roma women in Spain (Kale/Spanish Gypsies), this study aims to integrate key informants' opinions about the main actions needed to improve primary health care services' and professionals' responses to Roma women in an Intimate Partner Violence (IPV) situation. Methods Concept mapping study. A total of 50 (brainstorming phase), 36 (sorting and rating phase) and 16 (interpretation phase) participants from Roma civil society groups, primary health care professionals and other related stakeholders (social services, academic experts and other IPV NGOs representatives) from different cities in Spain were involved in the different study phases. Results Among the 55 action proposals generated, ten priority actions were identified through consensus as most important for improving primary health care's response to Romani women in an IPV situation, and these included primary, secondary and tertiary prevention activities. Conclusion Results indicated that efforts to address this challenge should take an integrated approach that reinforces the primary health care response to IPV in general, while also promoting more specific actions to address barriers to access that affect all Roma women and those who experience IPV in particular.